Biochar induced modifications in soil properties and its impacts on crop growth and production. (7th May 2021) - Murtaza, Ghulam; Ahmed, Zeeshan; Usman, Muhammad; Tariq, Waseem; Ullah, Zia; Shareef, Muhammad; Iqbal, Hassan; Waqas, Muhammad; Tariq, Akash; Wu, Yufeng; Zhang, Zhihao; Ditta, Allah
Abstract: Biochar is a carbonic recalcitrant product of biomass which is produced by pyrolysis process. In fact, biochar application has the potential to improve soil properties and crop productivity for long term scenarios compared to many other organic amendments. In this review we have tried to explore the role of biochar in the modification of soil properties (physical, chemical and biological), relevant effects of these changes on crop productivity and its future prospects and challenges by considering the existing literature. Addition of biochar as soil amendment has significantly influenced the soil physical, chemical and biological properties. Biochar application reduces the bulk density of soil, increased microbial activity, pH level and water holding capacity; but it varied according to soil texture. Furthermore, increase in soil porosity and infiltration rate has also been observed due to biochar addition. Simultaneously, biochar addition sometimes could have negative impacts on soil properties that appear in the form of crop productivity loss. This study will provide a clear picture about the role of biochar in modifying soil properties and its beneficial impacts on crop growth and yield.